Health Behaviors of the Young Adult U.S. Population: Behavioral Risk Factor Surveillance System, 2003 - Melissa McCracken, MPH; Ruth Jiles, PhD; Heidi Michels Blanck, PhD (Centers for Disease Control and Prevention, 2007)
IntroductionHealth-risk behaviors such as eating poorly, being physically inactive, and smoking contribute to the leading causes of morbidity and mortality in the United States and are often established during adolescence and young adulthood. The objectives of this study were to characterize the health-risk behaviors of young adults (aged 18-24 years) using a large population-based survey of Americans and to determine if behaviors of this group differ by weight category, as assessed by body mass index (BMI).MethodsPrevalence estimates for selected health-risk behaviors were calculated for respondents aged 18 to 24 years to the 2003 Behavioral Risk Factor Surveillance System (BRFSS). Respondents were categorized by BMI, and comparisons between sex and race and ethnicity were made within the overweight and obese categories.ResultsMore than three quarters (78.4%) of respondents consumed fewer than five fruits and vegetables per day, 43.2% reported insufficient or no physical activity, 28.9% were current smokers, 30.1% reported binge drinking, and 11.9% reported frequent mental distress. One quarter (26.1%) of respondents were overweight, and 13.6% were obese. Of obese young adults, 67.2% reported that they currently were trying to lose weight; however, only 24.3% reported having received professional advice to lose weight. More obese women (34.2%) than obese men (16.7%) reported having received professional advice to lose weight. Only 19.1% of obese non-Hispanic white respondents had received professional advice to lose weight compared with 28.0% of obese Hispanic respondents and 30.6% of obese non-Hispanic black respondents.ConclusionMany young adults engage in unhealthy behaviors, and differences exist in health-risk behaviors by BMI category and specifically by sex and race and ethnicity within BMI categories. The transition from adolescence to adulthood may be an opportune time for intervening to prevent future chronic disease.